Asymmetric Chlorination of 4-Substituted Pyrazolones Catalyzed by Chiral Copper Complexes - Chen, Xue-Yang; Jiang, Zhen-Hui; Ju, Wan-Zhen; Yin, Hao; Qi, Suo-Suo; Chu, Ming-Ming; Wang, Yi-Feng (Synlett, 2020)
A fast and highly enantioselective chlorination of 4-pyrazolones catalyzed by bis(oxazoline)–Cu(ClO4)2·6H2O complexes has been developed. Under the optimized conditions, a series of pyrazolones bearing stereogenic chlorine-attached carbon centers were obtained in moderate to high yields (up to 98%) and with enantioselectivities of up to 98% ee.
Keywords: asymmetric catalysis; copper catalysis; bisoxazolines; chlorination; pyrazolones